Prime Labeling of Union of Some Graphs (European Journal of Pure and Applied Mathematics, 2024)
A prime labeling of a graph G is a map from the vertex set of G to the set {1, 2, ..., |V (G)|} such that any two adjacent vertices in the graph G have labels that are relatively prime. In this paper, we discuss when the disjoint union of some graphs is a prime graph.
Keywords: Independence number; Wheels; Prime labeling; Prime graphs